1975
DOI: 10.1213/00000539-197511000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia for Thoracotomy Patients

Abstract: Severe postoperative pain, which may persist for up to 3 days and may lead to postoperative complications, due to the patient's inability to breathe deeply and cough, is frequently experienced in the area of the incision and chest tubes by thoracotomy patients. Eighteen patients undergoing routine thoracotomies were tested preoperatively for arterial blood gases and pulmonary function and given chest x-rays. Anesthesia consisted of thiopental, succinylcholine, N2O, enflurane, and pancuronium. Before incision c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
3

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 0 publications
1
33
0
3
Order By: Relevance
“…We also found that the addition of dextran to levobupivacaine provided better analgesia throughout the first postoperative day. The analgesic potentiating effects of dextran added to local anaesthetics are well known for infiltration anaesthesia, as well as nerve blocks and epidural anaesthesia . The present results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that the addition of dextran to levobupivacaine provided better analgesia throughout the first postoperative day. The analgesic potentiating effects of dextran added to local anaesthetics are well known for infiltration anaesthesia, as well as nerve blocks and epidural anaesthesia . The present results are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…We previously found that the addition of low‐molecular weight dextran to a local anaesthetic mixture with adrenaline reduced the absorption of adrenaline into the bloodstream . Furthermore, addition of various types of dextran, irrespective of the presence of adrenaline, has been found to prolong the effectiveness of local anaesthetics . Because of this, we speculated that addition of dextran to the local anaesthetic would reduce the increase in plasma concentration after combined single‐shot TAP and rectus sheath blocks in patients undergoing laparoscopic colectomy.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with other studies that have investigated the effects of a single intercostal nerve block. 11 13 15 25 In contrast to ICB, there is some evidence that a before operation paravertebral block may produce longer-acting analgesic effects due to a pre-emptive analgesic effect. This potential of paravertebral block has been described in the context of breast surgery 26 27 and thoracic surgery 28 29 and it has been speculated that one reason for this effect of paravertebral block might be that, in contrast to the ICB, it completely blocks transmission within the sympathetic chain.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous injection of local analgesia into the surgical incision site has been effectively used to reduce the side effects of narcotics [1-16]. The ON-Q pain management system (ON-Q PainBuster, referred to as ON-Q pump) created by the I Flow Corp. (Lake Forest, CA, USA) is a device that continuously administers local analgesia directly into the intra-abdominal surgical wound site.…”
Section: Introductionmentioning
confidence: 99%